2022
DOI: 10.1186/s12934-021-01736-7
|View full text |Cite
|
Sign up to set email alerts
|

Macular pigment-enriched oil production from genome-edited microalgae

Abstract: Background The photosynthetic microorganism Chlamydomonas reinhardtii has been approved as generally recognized as safe (GRAS) recently, this can excessively produce carotenoid pigments and fatty acids. Zeaxanthin epoxidase (ZEP), which converts zeaxanthin to violaxanthin, and ADP-glucose pyrophosphorylase (AGP). These are key regulating genes for the xanthophyll and starch pathways in C. reinhardtii respectively. In this study, to produce macular pigment-enriched microalgal oil, we attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Heterologous expression of this gene in C. reinhardtii boosted lutein content up to 8.9 mg/g which was 60% higher than the wild type under low light intensities of 75 mmol photons m −2 s −1 (Rathod et al, 2020). Recently, Song et al (2022), used CRISPR-Cas9 RNP mediated knock out strategies to delete the zeaxanthin epoxidase (ZEP) gene along with the ADP−glucose pyrophosphorylase (AGP) gene in the C. reinhardtii that is responsible for xanthophyll and starch biosynthesis in this microalga (Song et al, 2022). This double knock-out mutant enabled to accumulate 2.93 mg/g of lutein under optimal cultivation conditions (Song et al, 2022).…”
Section: Genetically Modified Microalgae For Enhanced Production Of L...mentioning
confidence: 99%
See 3 more Smart Citations
“…Heterologous expression of this gene in C. reinhardtii boosted lutein content up to 8.9 mg/g which was 60% higher than the wild type under low light intensities of 75 mmol photons m −2 s −1 (Rathod et al, 2020). Recently, Song et al (2022), used CRISPR-Cas9 RNP mediated knock out strategies to delete the zeaxanthin epoxidase (ZEP) gene along with the ADP−glucose pyrophosphorylase (AGP) gene in the C. reinhardtii that is responsible for xanthophyll and starch biosynthesis in this microalga (Song et al, 2022). This double knock-out mutant enabled to accumulate 2.93 mg/g of lutein under optimal cultivation conditions (Song et al, 2022).…”
Section: Genetically Modified Microalgae For Enhanced Production Of L...mentioning
confidence: 99%
“…Elucidation of carotenoids production in bacteria, algae, protist (Patel et al, 2022) and higher plants has progressed significantly, and it is expected that primary carotenoids biosynthesis in these species follows a similar process. Figure 1 depicts the lutein synthesis route in green algae (Chlorophyta), which is subdivided into the different stages (Huang et al, 2021;Kato et al, 2021;Lou et al, 2021;Xie et al, 2021;Song et al, 2022;Velmurugan and Kodiveri Muthukaliannan, 2022). The major metabolic pathway includes the synthesis of isopentenyl diphosphate (IPP), geranylgeranyl pyrophosphate, phytoene, and desaturation of phytoene into lycopene, followed by cyclisation and hydroxylation of lycopene to lutein.…”
Section: Biosynthesis Of Lutein In Microalgae By Native Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing interest in the new research areas such as integrated biosystems to produce H 2 in mixed-cultures and direct utilization of residual algal biomass as a primary input for hydrogen production by a consecutive anaerobic digestion stage. Interdisciplinary approaches, such as nanotechnology and electrochemistry, immobilization of cells on novel materials and utilization of wastewater resources as a convenient and renewable source of nutrients for H 2 production [ 65 ], were also reported [ 107 ]. Recently, Khanna et al reported a novel methodology regarding apo-hydrogenase activation via insertion of a synthetic cofactor in vivo, and the potential to create catalytically active “semi-synthetic” hydrogenases in living cells was demonstrated [ 108 ].…”
Section: Emerging Trends In Genetic Engineering Of Microalgae For Com...mentioning
confidence: 99%